2017
DOI: 10.1038/ejhg.2017.51
|View full text |Cite
|
Sign up to set email alerts
|

Improved imputation accuracy of rare and low-frequency variants using population-specific high-coverage WGS-based imputation reference panel

Abstract: Genetic imputation is a cost-efficient way to improve the power and resolution of genome-wide association (GWA) studies. Current publicly accessible imputation reference panels accurately predict genotypes for common variants with minor allele frequency (MAF)≥5% and low-frequency variants (0.5≤MAF<5%) across diverse populations, but the imputation of rare variation (MAF<0.5%) is still rather limited. In the current study, we evaluate imputation accuracy achieved with reference panels from diverse populations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
197
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 203 publications
(216 citation statements)
references
References 52 publications
18
197
1
Order By: Relevance
“…Interestingly, we observed that the HUNT WGS with 500 samples outperforms 1000G(Auton et al, 2015) for variants with MAF > 0.5%. These results are consistent with other studies with population specific reference panels(Mitt et al, 2017; Pistis et al, 2015). The subset of 1000 samples provides better imputation accuracy than 1000G(Auton et al, 2015) even for variants with MAF as low as 0.1% and comparable imputation accuracy to HRC(McCarthy et al, 2016) for variants with MAF > 0.5%.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, we observed that the HUNT WGS with 500 samples outperforms 1000G(Auton et al, 2015) for variants with MAF > 0.5%. These results are consistent with other studies with population specific reference panels(Mitt et al, 2017; Pistis et al, 2015). The subset of 1000 samples provides better imputation accuracy than 1000G(Auton et al, 2015) even for variants with MAF as low as 0.1% and comparable imputation accuracy to HRC(McCarthy et al, 2016) for variants with MAF > 0.5%.…”
Section: Resultssupporting
confidence: 93%
“…Although panel sizes are similar, the population-specific reference panel results in higher imputation accuracy than the mixed-ancestry 1000G panel (Auton et al, 2015) for variants with MAF ≥ 0.05%. This has also been observed by a recently published study on Estonians(Mitt et al, 2017). …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our comparisons on imputation strategies agree with recent literature (Deelen et al., ; Mitt et al., ; Pistis et al., ) in terms of the improvement in accuracy brought by a reference panel specific to the population under study. Mitt et al.…”
Section: Discussionsupporting
confidence: 90%
“…Mitt et al. () concluded that for certain outbred populations, such a panel can outperform an order of magnitude larger and more diverse reference panel (the HRC). We show that for a population isolate, an SSP can be far smaller and still outperform the HRC.…”
Section: Discussionmentioning
confidence: 99%